Stabilnost vertikalnih valobranov z upoštevanjem splošnih pravil Evrokoda 7 - Kvočka, Davor (Acta hydrotechnica, 2022)
Breakwaters are hydraulic structures designed to protect coastlines and coastal infrastructure, which are constantly exposed to the forces of the sea. Breakwaters are consequently subjected to a variety of hydrodynamic loads, wherefore breakwater stability must be prioritized during the breakwater design process. In this study, we examined the difference in the safety factor against overturning and sliding when the commonly used approach for calculating breakwater stability specified in BS 6349 was updated with the partial safety factors outlined in Eurocode 7. Our comparative analysis employed three different methods to calculate the hydrodynamic loads: the Sainflou method, the extended Goda method without the breakwater overtopping, and the extended Goda method with consideration of breakwater overtopping. The breakwater stability was calculated and compared for different breakwater widths, with constant wave parameters being used in all stability calculations. Within the stability calculations, we considered only overturning and sliding instability mechanisms. The obtained results show that there is no significant difference in the calculated breakwater stability coefficient between the two considered calculation procedures regardless of the method used for the calculation of the hydrodynamic loads. In order to develop a comprehensive approach for the calculation of breakwater stability based on the rules outlined in the Eurocodes, it would be necessary to determine the key processes and numerical models for calculating the stability of the foundation soil and to consider more precisely the impacts related to the breakwater shape and construction technique, construction materials, and local characteristics of the seabed.
Keywords: breakwater; BS 6349 standard; coastal engineering; Eurocode 7; Evrokod 7; hidrodinamične obremenitve; hydrodynamic load; obalno inženirstvo; stability; stabilnost; standard BS 6349; valobran